LEARNING CYCLE-7E MODEL TO INCREASE STUDENT’S CRITICAL THINKING ON SCIENCE - Hartono - (Semarang State University, 2013)
Penelitian ini bertujuan untuk memperoleh model pembelajaran Learning Cycle-7E yang dapat meningkatkan kemampuan berpikir kritis siswa dan menuntaskan hasil belajar siswa SMPN 21 Semarang terhadap matapelajaran IPA. Penelitian PTK ini dilaksanakan dalam dua siklus. Siklus pertama belum menunjukkan peningkatan yang maksimum. Aktivitas bertanya kepada guru, keseriusan melaksanakan tugas, dan persiapan dalam mengikuti pelajaran masih pada kategori sedang. Ketuntasan belajar secara individual dan klasikal belum memenuhi kriteria yang ditetapkan. Oleh sebab itu, aktivitas ini menjadi fokus perbaikan pada siklus berikutnya. Hasil pada siklus ke-dua menunjukkan peningkatan yang signifikan. Kemampuan berpikir kritis telah tumbuh, aktivitas bertanya pada guru dan keseriusan dalam melaksanakan tugas meningkat pada kategori tinggi. Ketuntasan belajar klasikal sebesar 79%, melebihi kriteria keberhasilan tindakan yang ditetapkan pada penelitian ini yaitu sebesar 75%. Hal ini berarti bahwa model pembelajaran Learning Cycle-7E dapat meningkatkan kemampuan berpikir kritis siswa, tanpa mengganggu hasil belajar kognitifnya. This research aimed to increase the students’ critical thinking by designing Learning Cycle- 7E which is suitable with the criteria set out in SJHS 21 Semarang. Thisclassroom action research was carried out in two cycles. In cycle-I, the students’ critical thinking was growing but not maximum, their activity during learning process was in medium category. That is why there were several aspects of students’ activity that need to be investigated. They were the students’courage to ask the teacher, their seriousness to do the assignments, and their readiness to learn as well as to prepare a question prior learning. The students’ average cognitive learning outcomes and the classical learning outcomes were not very satisfied. The result of the cycle-II showed a significant improvements. The students’ critical thinking was growing. The students’ activity learning process was in high level. Activity aspects which improve in cycle-II were the students’ willing to ask the teacher and seriousness in doing the task. The average of cognitive learning outcames has obtained the determined criteria and the cognitive classical mastery outcomes reached 79% which was higher than the one determined for the class, 75%. In the other hand, the students’ activity and critical thinking still develop without reduction in students’ cognitive ability